Surface property evolution and floatability response of dolomite to hydrogen-based mineral phase transformation - Daolai Tian; Zhidong Tang; Peng Gao; Pengcheng Tian; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

A review on the modified clay minerals for remediation of lead contaminated soil: mechanism analysis, modification methods, challenges and future prospects - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Selective adsorption of an eco-friendly depressant poly(acrylic acid-co-maleic acid) in columbite-dolomite flotation separation - Daolai Tian; Zhidong Tang; Peng Gao; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2026)

NearStitch: Robust near-surface image stitching for phenotyping - Yu Wang; Shichao Jin; Jianling Tang; Ke Wang; Shan Xu; Yanjun Su; Qinghua Guo; Dong Jiang; Yanfeng Ding; Frédéric Baret (Computers and Electronics in Agriculture, 2026)

MEHP exposure disrupts the self-renewal and differentiation of GC-1 cells by up-regulating m6A levels, leading to reproductive damage in immature rats - Yanjun Ding; Xiazhu Zhou; Yifan Hong; Jing Chen; Haohui Tang; Binrong Sun; Chunlan Long; Lianju Shen; Shengde Wu; Yuexin Wei; Guanghui Wei (Toxicology, 2026)

Antioxidant and hypoglycemic effects of phenolic-rich extracts from Eleutherococcus senticosus fruits using deep eutectic solvents - Yanjun Ren; Lizhu Zhao; Xiongfei Luo; Zhonghua Tang (Food Chemistry, 2026)

Heavy metal pollution in complex polymetallic ore processing: migration mechanism, treatment technologies, and future perspectives - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Environmental Research, 2026)

Interfacial-confined metal-support interaction in rare-earth oxide enables selective high-valent iron-oxo species generation for efficient water purification - Min Tang; Baoleerhu Borjigin; Wu Liu; Qi Zhang; Yanjun Zhao; Rui Peng; Jinquan Wan (Chemical Engineering Journal, 2026)

Bioaerosol emissions during initial food waste degradation: Emission dynamics, dispersion modeling, and health risk assessment - Yingchao Liu; Qiange Tang; Yanjun Liu; Zhanhong Yang; Jianbing Wang (Journal of Hazardous Materials, 2026)

Process design and optimization for resource-efficient recovery of Fe, P, and Ti from a low-grade complex iron ore - Shiteng Qin; Xiaokun Li; Bing Zhao; Peng Gao; Yanjun Li; Zhidong Tang (Minerals Engineering, 2026)

Hydrogen-based suspension roasting for efficient utilization of high-phosphorus oolitic hematite: Selective reduction mechanism and metallization behavior - Xuesong Sun; Yanjun Li; Zhidong Tang; Jianwen Yu; Yize Guo; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

Rendering regenerated cellulose films superhydrophobic via modulated silanization in regeneration process - Xinhua Dong; Ya Li; Junming Wang; Chunjie Ye; Huining Xiao; Yanjun Tang (Journal of Environmental Chemical Engineering, 2026)

Synergistic effect of cocatalyst engineering and radical regulation toward high selectivity in one-step methane conversion - Chuan Yu; Mingli Fu; Keke Tang; Yanjun Li; Lei Liu; Chen Yang; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Coral-based reconstruction of interannual and decadal SST variability in the northern South China Sea during the mid-Holocene - Zhiheng Wu; Tingli Yan; Rui Tang; Ben Wang; Yanjun Mei; Ning Zhao (Geo-Marine Letters, 2026)

Decoupling environmental drivers of bioaerosol emissions during food waste degradation - Yanjun Liu; Haiwen Ning; Qiange Tang; Yanfeng Zhang; Zhuowen Chen; Qingfei Li; Jianbing Wang; Zhanhong Yang (Waste Management, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

Microplastics affect the quality of Cucumis melo. L by regulating the jasmonic acid signaling pathway - Tianyu Liu; Jinpeng Zhang; Mao Xu; Zhengkun Zhang; Yanjun Li; Xuedong Tang; Ling Liu; Yong Yu (Environmental Pollution, 2026)

Corrigendum to “Ultrafast improvement of cellulose accessibility via non-dissolving pretreatment with LiBr·3H2O under room temperature” [Carbohydrate Polymers 284 (2022) 119180] - Zhonglei Huang; Guang Yu; Chao Liu; Meiyan Wu; Yanjun Tang; Bin Li; Hui Peng (Carbohydrate Polymers, 2026)

Earthworm activity and its gut microbiota drive the valorization of municipal sewage sludge by enhancing aggregate stability and phytohormone content - Yunxiang Xu; Jin Wang; Guoxun Su; Yizhao Wu; Jiayi Li; Huaixiang Zhou; Xiaoying Yi; Li Tang; Yanjun Shen; Yinsheng Li; Qi Zhao (Journal of Environmental Chemical Engineering, 2026)

Influence and optimization of hydrogen-based mineral phase transformation on grinding characteristics of polymetallic oxide and recovery of valuable elements by response surface methodology - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Minerals Engineering, 2025)

Acoustic emission-based damage assessment and failure mechanism analysis on CFST columns with different joint configurations under compression-bending loads - Enchao Rong; Junfu He; Liqiang Tang; Kaizhong Xie; Yanjun Chang (Engineering Structures, 2025)

Comparative study of injectable and stimuli-responsive hydrogels reinforced with cellulose nanofibers and chitosan for controlled drug delivery - Yaoting Liang; Tong Luo; Feiyun Li; Jifu Wang; Yanjun Tang (Chemical Engineering Journal, 2025)

Tannic acid-assisted construction of ZIF-8/cellulose nanofiber composite aerogels for efficient oil adsorption and oil/water separation - Wenting Huang; Yahui Tao; Ya Li; Tong Luo; Yanjun Tang (Carbohydrate Polymers, 2025)

Light-driven release of 6PPD and formation of 6PPD-Q from tire and road wear particles: Mechanisms and cytotoxicity - Danfeng Zhang; Bo Yin; Wen Zhang; Shiyu Wei; Puxing Zhang; Tianyuan Su; Yanjun Liu; Xiwang Tang; Han Wang; Chengfang Yang; Zhuozhi Ouyang; Guining Lu; et al. (Journal of Hazardous Materials, 2025)

Effect of egg yolk component and its enzymatic hydrolysate on the flavor and texture of walnut cake - Tingting Tang; Qing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Effects of enzyme treatment on structural characteristics of egg yolk, plasma and granule and their correlation with flavor components - Tingting Tang; Wen Yu; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Strategy to kill two birds with one stone: Contribution of hydrogen-based mineral phase transformation on enhancing the grinding and flotation characteristics of bastnaesite and fluorite - Pengcheng Tian; Jian Zhang; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Process Safety and Environmental Protection, 2025)

Mobilization of water-dispersible colloidal chromium and nickel in basalt-derived paddy soils: Role of Fe (hydr)oxides and organic matter - Ting Liu; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Zhuobiao Ni; Qingqi Lin; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Sustainable treatment of solid titanium-gypsum-waste using acidic titanium-white-wastewater to produce high-value α-hemihydrate gypsum - Yuru Wang; Mengqi Xiang; Jiangmei Yi; Ye Wang; Wenxiang Tang; Yanjun Zhong; Hua Meng; Xiaodong Ma; Zhiyuan Chen (Hydrometallurgy, 2025)

Impact of anti-solvents on the characteristics of hemicellulose fractionated from bleached bamboo pulp using lithium bromide hydrates - Xuejing Yu; Runzhu Gong; Meiyan Wu; Yufa Gao; Qian Li; Fang Zhang; Mehdi Rahmaninia; Bin Li; Yanjun Tang (Carbohydrate Polymers, 2025)

Effect of adding different egg yolk oil on the flavor and physicochemical properties of mayonnaise - Xuejing Gao; Tingting Tang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Preparation of temperature-dependent flux controllable cellulose nanofiber-based films and their application in oil-water separation - Feiyun Li; Jinxian Shan; Helin Li; Hongming Lou; Yanjun Tang (Carbohydrate Polymers, 2025)

The performance of an embankment over soft clay under rainfall with tension cracks at soil-pile interface caused by lateral deformation - Xing Wei; Shitao Cheng; Yanjun Li; Rui Chen; Zijian Wang; Fan Tang; Bingkun Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Single-B-cell cloning and recombinant antibodies generation to analyze the antigenicity of porcine reproductive and respiratory syndrome virus nonstructural protein 12 - Hongyong Duan; Chaozhi Tang; Song Han; Nan Yang; Shumao Wang; Fei Gao; Yanjun Zhou; Guangzhi Tong; Kuan Zhao; Liwei Li (Veterinary Microbiology, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

Study of the initiating and resisting mechanisms of toppling deformations in anti-inclined rock slopes - Yibing Ning; Huiming Tang; Jianbing Peng; Yanjun Shen; John V. Smith; Tao Ding (Bulletin of Engineering Geology and the Environment, 2025)

Constructing of ultrahigh pH-responsive polycarboxylic copolymers for enhanced recycling cellulase from enzymatic hydrolyzate of corncob resides - Huinan Liang; Feiyun Li; Hongming Lou; Yanjun Tang (Fuel, 2025)

Electrocatalytic conversion of nitrate to ammonia on the oxygen vacancy engineering of zinc oxide for nitrogen recovery from nitrate-polluted surface water - Wenyang Fu; Yanjun Yin; Shuxian He; Xiangyi Tang; Yinan Liu; Fei Shen; Yan Zou; Guangming Jiang (Environmental Research, 2025)

Rigid polymethacrylimide composites foam for efficient electromagnetic dissipation and infrared stealth - Zihang Zhang; Zixuan Wang; Yanjun Zhang; Peiyuan Zou; Mingyang Zhu; Shuangshuang Li; Xinwei Tang; Yezi Lu; Wei Li; Kaixin Lai; Wei Hong; Yufei Li; et al. (Chemical Engineering Journal, 2025)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Extraction of egg yolk lipids via salt-induced synergistic heat treatment: Fabrication, characterization and flavor analysis - Xuejing Gao; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Effects of non-covalently bound polyphenols/vitamins on the structure and functional characteristics of egg yolk powder - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

High-performance cellulose/thermoplastic polyurethane composites enabled by interaction-modulated cellulose regeneration - Yuhui Ci; Dong Lv; Xiangjian Yang; Haishun Du; Yanjun Tang (Carbohydrate Polymers, 2024)

Cobalt single-site molecular Catalyst-mediated electrochemical Hydrodechlorination for detoxification of halogenated Antibiotics: Performance, reaction pathway and mechanism - Yinan Liu; Xiangyi Tang; Fei Shen; Jiahong Zou; Yanjun Yin; Zhaojie Jiao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Guangming Jiang; Hong Liu (Chemical Engineering Journal, 2024)

Deficit irrigation combined with a high planting density optimizes root and soil water–nitrogen distribution to enhance cotton productivity in arid regions - Fengquan Wu; Qiuxiang Tang; Jianping Cui; Liwen Tian; Rensong Guo; Liang Wang; Zipiao Zheng; Na Zhang; Yanjun Zhang; Tao Lin (Field Crops Research, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Four-in-one multifunctional self-driven photoelectrocatalytic system for water purification: Organics degradation, U(VI) reduction, electricity generation and disinfection against bacteria - Sixuan Cai; Yanjun Wen; Qingyan Zhang; Qingming Zeng; Qingqing Yang; Beibei Gao; Guolong Tang; Qingyi Zeng (Science of The Total Environment, 2024)

Comparison and analysis of mechanism of β-lactoglobulin self-assembled gel carriers formed by different gelation methods - Xiaolin Meng; Ying Wu; Wangruiqi Tang; Lei Zhou; Wei Liu; Chengmei Liu; Sangeeta Prakash; Yanjun Zhang; Junzhen Zhong (Food Chemistry, 2024)

Investigation into the impact of enzyme treatment on the structural characteristics of egg yolk protein and its correlation with flavor constituents - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Facile dissolution of cellulose by superbase-derived ionic liquid using organic solvents as co-solvents at mild temperatures - Yuhui Ci; Yunqian Ma; Tianying Chen; Feiyun Li; Yanjun Tang (Carbohydrate Polymers, 2024)

A self-driven solar coupling system with TiO2@MXene cathode for effectively eliminating uranium and organics from complex wastewater accompanying with electricity generation - Lulin Guo; Yi-Lin Liu; Qingming Zeng; Chao Zhang; Yanjun Wen; Qingyan Zhang; Guolong Tang; Qingsong Zhang; Qingyi Zeng (Journal of Hazardous Materials, 2024)

Effects of cholesterol removal treatment on the flavor and physicochemical properties of hot gel egg yolk - Tingting Tang; Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Synthesis of bifunctional thermal response promoters for improved high-solids enzymatic hydrolysis of corncob residues - Feiyun Li; Haohao Li; Hongming Lou; Fubao Sun; Yanjun Tang (Bioresource Technology, 2023)

Root predominant overexpression of iaaM and CKX genes promotes root initiation and biomass production in citrus - Dan Tang; Yanjun Li; Longmei Zhai; Wei Li; Rahul Kumar; Huseyin Yer; Hui Duan; Baoping Cheng; Ziniu Deng; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Promoting initiation and biomass production of roots is significant for plant-based industries including using roots as bioreactors. Two citrus genotypes, Carrizo and US-897, were used as model plants to test the effects of root-predominantly overexpressed the iaaM (indoleacetic acid-tryptophan monooxygenase) gene and a CKX (a cytokinin oxidase/dehydrogenase) gene. The iaaM transgenic lines exhibited markedly faster root initiation, more root numbers, and higher root biomass compared to their wild-type counterparts. The transgenic iaaM + CKX plants also exhibited similar phenotypes, albeit to a lesser extent than the iaaM plants. Molecular analysis revealed an auxin-responsive CsGH3.1 gene was up-regulated in the iaaM roots and iaaM + CKX roots, and a cytokinin-responsive gene CsARR5 gene was down-regulated in the iaaM + CKX roots. Our results demonstrate that root predominant overexpression of the iaaM or both the iaaM and CKX genes drastically enhances the initiation, growth and biomass production of roots. These results provide additional support that manipulation of auxin and cytokinin levels in roots via transgenic or gene-editing technologies may benefit production of high-value secondary metabolites using roots as bioreactors and also improve rooting of recalcitrant plant species.

Mechanism study on a recyclable and clean process for boron removal from industrial-grade silicon using CrMnFeNiMe high-entropy alloy - Yong Liu; Zhihua Zeng; Yanjun Zhong; Wenxiang Tang; Ye Wang; Zhiyuan Chen; Wenhui Ma; Kazuki Morita (Journal of Cleaner Production, 2023)

Co-assembly of stearoylated cellulose nanocrystals and GO (or CNTs) for the construction of superhydrophobic hierarchical structure with enhanced photothermal conversion - Wei Huang; Xiangyu Tang; Wuming Fan; Qianqian Sun; Yonggui Wang; Zefang Xiao; Yanjun Xie (Carbohydrate Polymers, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Comparative study of sediment phosphorus immobilization via the addition of lanthanum-modified and thermal-modified drinking water treatment sludge - Fei Sun; Yu Chen; Liwenze He; Jingxiang Tang; Yanjun Li (Environmental Science and Pollution Research, 2023)

Solar-driven wastewater treatment coupled with hydrogen and electricity production via a bismuth-doped TiO2 nanorod array - Beibei Gao; Jing Tan; Yuhan Cao; Qingsong Zhang; Yanjun Wen; Qingming Zeng; Guolong Tang; Junwen Lv; Lin Wang; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2023)

Pressure melting of pore ice in frozen rock under compression - Ting Wang; Hailiang Jia; Qiang Sun; Tuo Lu; Liyun Tang; Yanjun Shen (Cold Regions Science and Technology, 2023)

Thermal gelation and digestion properties of hen egg white: Study on the effect of neutral and alkaline salts addition - Junhua Li; Weijian Zhang; Tingting Tang; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Food Chemistry, 2023)

Mapping China’s planted forests using high resolution imagery and massive amounts of crowdsourced samples - Kai Cheng; Yanjun Su; Hongcan Guan; Shengli Tao; Yu Ren; Tianyu Hu; Keping Ma; Yanhong Tang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Gel properties of soy protein isolate-potato protein-egg white composite gel: Study on rheological properties, microstructure, and digestibility - Yuanqi Lv; Lilan Xu; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Ming Zhang; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2023)

Cobalt induces neurodegenerative damages through impairing autophagic flux by activating hypoxia-inducible factor-1α triggered ROS overproduction - Jianping Tang; Yanjun Li; Xu Liu; Guangxia Yu; Fuli Zheng; Zhenkun Guo; Yating Zhang; Wenya Shao; Siying Wu; Huangyuan Li (Science of The Total Environment, 2023)

Scalable fabrication of efficient and recycling wood residue-derived sponge for crude oil adsorption - Ying Shang; Runan Gao; Yaoxing Wang; Xiaofei Dong; Xueqi Li; Jianfu Tang; Xuan Wang; Jiuqing Liu; Yanjun Xie; Jian Li; Wentao Gan (Journal of Hazardous Materials, 2023)

Flotation de-inking for recycling paper: contrasting the effects of three mineral oil-free offset printing inks on its efficiency - Shujie Yang; Jianbin Shen; Tiefei He; Chao Chen; Junming Wang; Yanjun Tang (Environmental Science and Pollution Research, 2022)

Projecting future changes in extreme climate for maize production in the North China Plain and the role of adjusting the sowing date - Dengpan Xiao; Huizi Bai; De Li Liu; Jianzhao Tang; Bin Wang; Yanjun Shen; Jiansheng Cao; Puyu Feng (Mitigation and Adaptation Strategies for Global Change, 2022)

Hypoxia preconditioning improves structure and function of astrocytes mitochondria via PGC-1α/HIF signal - Yue Wu; Cunlin Gu; Lu Huang; Yuanqing Zhao; Yanjun Tang; Hongqian Zhao; Qiong Wu (Journal of Biosciences, 2021)

Impact of COMT haplotypes on functional connectivity density and its association with the gene expression of dopamine receptors - Jie Tang; Yanjun Li; Jiayuan Xu; Wen Qin; Qian Su; Qiang Xu; Bing Liu; Tianzi Jiang; Chunshui Yu (Brain Structure and Function, 2019)

Depletion of collagen by losartan to improve tumor accumulation and therapeutic efficacy of photodynamic nanoplatforms - Yuxia Tang; Ying Liu; Shouju Wang; Ying Tian; Yanjun Li; Zhaogang Teng; Guangming Lu (Drug Delivery and Translational Research, 2019)

Peak shear strength prediction for discontinuities between two different rock types using a neural network approach - Qiong Wu; Yanjun Xu; Huiming Tang; Kun Fang; Yaofei Jiang; Chaoyuan Liu; Xiaohan Wang (Bulletin of Engineering Geology and the Environment, 2019)

How up-scaling of remote-sensing images affects land-cover classification by comparison with multiscale satellite images - Kaijian Xu; Qingjiu Tian; Yanjun Yang; Jibo Yue; Shaofei Tang (International Journal of Remote Sensing, 2019)

Identification of movement characteristics and causal factors of the Shuping landslide based on monitored displacements - Qiong Wu; Huiming Tang; Xiaohan Ma; Yiping Wu; Xinli Hu; Liangqing Wang; Robert Criss; Yi Yuan; Yanjun Xu (Bulletin of Engineering Geology and the Environment, 2019)

Clinical evaluation of a panel of multiplex quantitative real-time reverse transcription polymerase chain reaction assays for the detection of 16 respiratory viruses associated with community-acquired pneumonia - Dan Zhang; Haiyan Mao; Xiuyu Lou; Junhang Pan; Hao Yan; Hongfeng Tang; Yan Shu; Yun Zhao; Xiaoli Cheng; Hong Tao; Yanjun Zhang; Xuejun Ma (Archives of Virology, 2018)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots - Rongjun Fang; Fengyao Wu; Ailan Zou; Yu Zhu; Hua Zhao; Hu Zhao; Yonghui Liao; Ren-Jie Tang; Tongyi Yang; Yanjun Pang; Xiaoming Wang; Rongwu Yang; et al. (Plant Molecular Biology, 2016)

Division of the stages of coalbed methane desorption based on the Langmuir adsorption isotherm - Meng YanJun; Tang DaZhen; Qu YingJie; Xu Hao; Li Yong (Arabian Journal of Geosciences, 2015)

Distribution of stable carbon isotope in coalbed methane from the east margin of Ordos Basin - Yong Li; DaZhen Tang; Yi Fang; Hao Xu; YanJun Meng (Science China Earth Sciences, 2014)

Coalbed methane produced water in China: status and environmental issues - Yanjun Meng; Dazhen Tang; Hao Xu; Yong Li; Lijun Gao (Environmental Science and Pollution Research, 2014)

Effects of Cow Dung Biochar Amendment on Adsorption and Leaching of Nutrient from an Acid Yellow Soil Irrigated with Biogas Slurry - Yanjun Guo; Hua Tang; Guangdi Li; Deti Xie (Water, Air, & Soil Pollution, 2014)

Antitumor and antimetastatic activities of vesicular stomatitis virus matrix protein in a murine model of breast cancer - Wei Shi; Qingqing Tang; Xiancheng Chen; Ping Cheng; Peidu Jiang; Xiaomei Jing; Xiang Chen; Ping Chen; Yongsheng Wang; Yuquan Wei; Yanjun Wen (Journal of Molecular Medicine, 2009)

The phosphorylation status of merlin in sporadic vestibular Schwannomas - Zhaoyan Wang; Yanjun Lu; Juanjuan Tang; Haojie Wang; Hao Wu (Molecular and Cellular Biochemistry, 2009)

Flexible design of a rock slope abutment at the Wuqiangxi Hydroelectric Power Station - Yanjun Shang; Hyeong-Dong Park; Zhifa Yang; Da’an Liu; Chunhua Tang (Bulletin of Engineering Geology and the Environment, 2006)

Variation of fluxes of water vapor, sensible heat and carbon dioxide above winter wheat and maize canopies - Zhang Yongqiang; Shen Yanjun; Yu Qiang; Liu Changming; A. Kondoh; Tang Changyuan; Sun Hongyong; Jia Jinsheng (Journal of Geographical Sciences, 2002)